Microwave-assisted extraction of phenolic compounds from Commiphora gileadensis leaf and their characterization - Aiman A. Bin Mokaizh; Abdurahman Hamid Nour; Chinonso Ishmael Ukaegbu (Results in Engineering)
Commiphora gileadensis (C. gileadensis) is a plant traditionally used in many parts of the world for medicinal purposes. However, the benefits of this plant are yet to be uncovered due to the use of conventional extraction methods during its extraction. Hence, there is a need for more efficient and environment-friendly extraction methods for optimum recovery of the bioactive components of C. gileadensis. This study aims to evaluate the impact of microwave-assisted extraction (MAE) process parameters (individually and in combination) on the recovery of phenolic compounds from C. gileadensis leaf. One-Factor-At-a-Time (OFAT) optimization method was used in this work to study the impact of varying the MAE process parameters (sample: solvent ratio, microwave power, ethanol concentration, and extraction temperature) on the optimum yield of phenolic compounds. The obtained phenolic compounds were characterized using Gas chromatography-mass spectrometry (GC–MS) for tentative identification of the component phytochemicals of the extract. The results showed that the optimal process condition of microwave power at 300 W, solvent/sample ratio of 1:10 g/mL, solvent concentration of 40 % v/v, and extraction temperature of 40 °C gave the maximum extraction yield of 33.20 ± 0.42 % w/w, total phenolic content (TPC) of 114.65 ± 3.14 mg GAE/g d.w., and total flavonoids content (TFC) of 37.56 mg QE/g d.w.). Furthermore, the GC-MS analysis identified 25 phenolic compounds with good antioxidant activities from the extracts. Therefore, MAE is considered a non-conventional green method for improved extraction of phenolic compounds from C. gileadensis leaf compared to the existing conventional extraction methods.